Constraints on the Abundance of Primordial Black Holes from X-Ray Quasar Microlensing Observations: Substellar to Planetary Mass Range - A. Esteban-Gutiérrez; E. Mediavilla; J. Jiménez-Vicente; J. A. Muñoz (The Astrophysical Journal, 2023)
We use X-ray observations of quasar microlensing (sensitive to smaller compact objects than in the optical) to study the possible presence of a population of low mass black holes (BHs; from ∼10 ^−3 M _⊙ to 10 ^−1 M _⊙ ) in lens galaxies. We compare these observations with microlensing magnification simulations of a mixed population of stars and BHs plus a smooth matter component. We estimate the individual mass fractions of both stars and BHs for three different BH masses in the range of substellar to planetary masses. Our Bayesian analysis indicates that the contribution of BHs is negligible in the substellar mass range but that a population of BHs of planetary mass ( M ≲ 10 ^−3 M _⊙ ) could pass unnoticed to X-ray microlensing. We provide new upper limits to the contribution of BHs to the fraction of dark matter based on both, the quasar microlensing data in the X-ray band, and our previous estimates in the optical of intermediate-mass BHs with an additional upper limit at M = 3 M _⊙ .